The Javanese War: Prince Diponegoro and the Legendary Rebellion Movement against the Dutch Colonial Regime - Bani Sudardi; Istadiyantha Istadiyantha (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
In the Kasunanan of Yogyakarta, the Diponegoro War took place from 1825 to 1830. A central figure in the incident, namely, Prince Diponegoro, took the name of this war. Unlike the life of royal princes in general, Prince Diponegoro did not spend his time in various pleasant and luxurious forms of life. The Prince of Diponegoro had been living outside the palace since a young age and was busy deepening various understandings, including deepening the Islamic teachings. His personal life reflects a type of life filled with piety and misticism, due to this way of life and a lot of contact with Ulama. Even the prince was known as Ksatria-ulama by the observers. As someone overflowing with piety and modesty in practice. Then when he led the revolution against the Dutch colonial government, there were many expectations and perceptions associated with the movement. There were a number of hopes raised on the shoulders of Prince Diponegoro, in accordance with the circumstances at that time when the group was in a difficult position, oppressed both in the social, political and economic fields due to various colonialism. From this dream, then, Prince Diponegoro adhered to the character of Mahdism, that is to say, the dream of a future full of prosperity, stability and tranquility, both in social, political and economic life. From this, the meaning emerged that the Diponegoro War was a movement known as mahdism.